Analisis Tingkat Pemahaman Dan Penerapan Pengelolaan Limbah B3 Pada Bengkel Motor Di Kota Makassar - Aminuddin, Aminuddin; Z, Muhsin; Romadin, Achmad (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2024)
Hazardous and toxic (B3) waste management is an important aspect in preserving the environment and public health in urban areas, as this waste includes a variety of materials that can cause serious damage if not managed properly. The research method used is mixed method, using data collection interviews, observation, documentation and questionnaire studies. Based on the research results obtained: (1) knowledge of hazardous waste in Makassar city motorcycle repair shops shows quite good results with an average value of 4.15 which falls into the "Good" category with a percentage of 24.66%; (2) Hazardous waste treatment is very important to reduce negative impacts on the environment and human health, including the process of identification, classification, collection, and treatment with appropriate methods, such as recycling and chemical neutralization; and (3) Utilization of hazardous waste, such as used oil, as a lubricant, coolant, and household stove fuel, provides economic benefits and supports more environmentally friendly and sustainable workshop operations.